2006
DOI: 10.7589/0090-3558-42.2.415
|View full text |Cite
|
Sign up to set email alerts
|

Possible Vector Dissemination by Swift Foxes following a Plague Epizootic in Black-tailed Prairie Dogs in Northwestern Texas

Abstract: To determine whether swift foxes (Vulpes velox) could facilitate transmission of Yersinia pestis to uninfected black-tailed prairie dog (Cynomys ludovicianus) colonies by acquiring infected fleas, ectoparasite and serologic samples were collected from swift foxes living adjacent to prairie dog towns during a 2004 plague epizootic in northwestern Texas, USA. A previous study (1999-2001) indicated that these swift foxes were infested almost exclusively with the flea Pulex irritans. Black-tailed prairie dogs exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…, O. tuberculata cynomuris, and Pulex simulans. Except for P. simulans, which is also found on carnivores, the fleas associated with prairie dogs are rarely found on other mammals (Brinkerhoff et al 2006, McGee et al 2006, Salkeld et al 2007).…”
Section: Figure 1 Prairie Dogs (Left) Are Burrowing Herbivorous DImentioning
confidence: 99%
See 1 more Smart Citation
“…, O. tuberculata cynomuris, and Pulex simulans. Except for P. simulans, which is also found on carnivores, the fleas associated with prairie dogs are rarely found on other mammals (Brinkerhoff et al 2006, McGee et al 2006, Salkeld et al 2007).…”
Section: Figure 1 Prairie Dogs (Left) Are Burrowing Herbivorous DImentioning
confidence: 99%
“…pestis-positive fleas have yet to be found on carnivores (McGee et al 2006, Salkeld and Stapp 2006, Salkeld et al 2007). It is worth noting that prairie dog-and carnivore-mediated dispersal of Y. pestis are not mutually exclusive, and the importance of carnivores in the spread of plague will likely vary, depending on the species involved (Brinkerhoff et al 2009).…”
Section: Figure 4 a Time Series Of The Size Of Nine Prairie Dog Colomentioning
confidence: 99%
“…The Pulex genus comprises six species (Whithing et al, 2008), but only two of them, P. simulans and P. irritans, are reported to infest wild carnivore hosts (Harrison et al, 2003;McGee et al, 2006;Salkeld et al, 2007;Gabrel et al, 2009;Dobler & Pfeff er, 2011). In concordance with our fi ndings, P. irritans usually predominates and is often the most common fl ea on the genus Vulpes, while P. simulans is typically the most common fl ea on gray foxes (Urocyon cinereoargenteus) and coyotes (Canis latrans) (Harrison et al, 2003;McGee et al, 2006;Salkeld et al, 2007;Gabrel et al, 2009;Dobler & Pfeff er, 2011). As might be expected, we found that P. irritans had a broader host distribution than other species.…”
Section: Discussionmentioning
confidence: 99%
“…Also, researchers have identifi ed wild canids as carriers of Yersinia pestis (the causal agent of plague) among prairie dog (Cynomys spp.) colonies (McGee et al, 2006). Many fl ea species that function as important vectors of fl ea-borne diseases (e.g., Pulex spp., Oropsylla spp., and Ctenocephalides spp.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation